Congenital hepatic fibrosis associated with Gilbert's syndrome and cholelithiasis in a pediatric patient – The crucial role of liver biopsy in diagnostic process - Lipiński, Patryk; Cielecka-Kuszyk, Joanna; Pawłowska, Joanna; Wicher, Dorota; Jankowska, Irena (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Congenital hepatic fibrosis constitutes a ductal plate malformation of the small interlobular bile ducts resulting in progressive fibrosis of the liver. Isolated form of the disease is rare, most commonly is accompanied by other entities comprising the group of fibropolycystic diseases. Clinical presentation of congenital hepatic fibrosis is variable and nonspecific, making the initial diagnosis difficult. Besides of its invasiveness, the liver biopsy is still considered as a gold standard in diagnostic process. We report an undescribed so far coexistence of biopsy proven congenital hepatic fibrosis with cholelithiasis and Gilbert's syndrome in a pediatric patient.